Genomic redistribution of GR monomers and dimers mediates transcriptional response to exogenous glucocorticoid in vivo - Lim, Hee-Woong; Uhlenhaut, N. Henriette; Rauch, Alexander; Weiner, Juliane; Hübner, Sabine; Hübner, Norbert; Won, Kyoung-Jae; Lazar, Mitchell A.; Tuckermann, Jan; Steger, David J. (Genome Research, 2015)
Glucocorticoids (GCs) are commonly prescribed drugs, but their anti-inflammatory benefits are mitigated by metabolic side effects. Their transcriptional effects, including tissue-specific gene activation and repression, are mediated by the glucocorticoid receptor (GR), which is known to bind as a homodimer to a palindromic DNA sequence. Using ChIP-exo in mouse liver under endogenous corticosterone exposure, we report here that monomeric GR interaction with a half-site motif is more prevalent than homodimer binding. Monomers colocalize with lineage-determining transcription factors in both liver and primary macrophages, and the GR half-site motif drives transcription, suggesting that monomeric binding is fundamental to GR's tissue-specific functions. In response to exogenous GC in vivo, GR dimers assemble on chromatin near ligand-activated genes, concomitant with monomer evacuation of sites near repressed genes. Thus, pharmacological GCs mediate gene expression by favoring GR homodimer occupancy at classic palindromic sites at the expense of monomeric binding. The findings have important implications for improving therapies that target GR.
10.1101/gr.188581.114